Our Experience of Passage on the B-Theory - Deng, Natalja (Erkenntnis, 2013)
Elsewhere I have suggested that the B-theory includes a notion of passage, by virtue of including succession. Here, I provide further support for that claim by showing that uncontroversial elements of the B-theory straightforwardly ground a veridical sense of passage. First, I argue that the B-theory predicts that subjects of experience have a sense of passivity with respect to time that they do not have with respect to space, which they are right to have, even according to the B-theory. I then ask what else might be involved in our experience of time as passing that is not yet vindicated by the B-theoretic conception. I examine a recent B-theoretic explanation of our 'illusory' sense of passage, by Robin Le Poidevin, and argue that it explains away too much: our perception of succession poses no more of a problem on the B-theory than it does on other theories of time. Finally, I respond to an objection by Oreste Fiocco that a causal account of our sense of passage cannot succeed, because it leaves out the 'phenomenological novelty' of each moment.